REPOSISI KETETAPAN MAJELIS PERMUSYAWARATAN RAKYAT DALAM TATANAN PENYELENGGARAAN BEREGARA - Surahman Surahman (Fakultas Hukum Universitas Muhammadiyah Palu, 2018)
State administration in the Unitary State of the Republic of Indonesia shall be implemented in accordance with the Constitution of the State of the Republic of Indonesia Year 1945. The 1945 Constitution has been amended four times. One of the fundamental changes is the change of Article 1 paragraph (2) which previously reads